Anthropometric measures and blood pressure in school children - Deise Cristiane Moser; Isabela de Carlos Back Giuliano; Ana Cláudia Kapp Titski; Anelise Reis Gaya; Manuel João Coelho-; Neiva Leite (Brazilian Society of Pediatrics, 2013)
Objective: To investigate the association of blood pressure and body mass index, waist circumference, waist-to-height ratio and triceps skinfold, in children and adolescents in Curitiba, state of Paraná, Brazil. Methods: Cross-sectional study with a random sample of 1,441 students from public schools, aged from10 to 16 years (655 boys and 786 girls). The following indicators were assessed: weight, height, waist circumference, triceps skinfold, systolic and diastolic blood pressures, pubertal stage, and socioeconomic status. Pearson correlation tests and multivariate logistic regression were used, considering p < 0.05. Results: We found weak correlations among all the anthropometric parameters and systolic and diastolic levels, with coefficients values ranging from 0.18 to 0.28 (p < 0.001). In multivariate analysis, only body mass index [odds ratio (OR) = 2.9; 95% confidence interval (95%CI) 1.9-4.5] and triceps skinfold (OR = 1.9; 95%CI 1.3-3.1) were found as predictors of high blood pressure, regardless of abdominal adiposity, sexual maturation and socioeconomic status. Conclusion: Total body adiposity seems to be a better predictor of high blood pressure risk than abdominal fat in this population.